التوجه نحو تبني المسؤولية الاجتماعية كأحد مرتكزات استدامة المشروع المقاولاتي -بين المقومات والمعوقات- - زين يونس (Finance and Business Economies Review, 2017)
In light of the current economic changes it became necessary on contracting to bear its social responsibility as one of the actors economic partners and their contribution to sustainable development. The primary goal of this intervention to highlight the importance and inevitability of adopting entrepreneurial social responsibility under the requirements of sustainable development without compromising the economic effectiveness of any adoption of policies and programs that are compatible between thought Entrepreneurial profit and the requirements of sustainable development, and we have tried to highlight the obstacles to achieving this goal.